Therapeutic Management of Preputial Prolapse in Gir Bulls - Vadalia, J.V.; Tank, P.H.; Patel, J.S.; Fefar, D.T.; Padaliya, N.R. (The Indian Journal of Animal Reproduction, 2021)
Traumatic injury to prepuce followed by its contamination and infection are the  main etiologies for the preputial prolapse in Gir bulls. All the six breeding Gir  bulls under study had common anatomical/structural deformities of the preputial  sheath. The medical/clinical management was carried out in bulls affected with 2nd degree preputial prolapse. The animals were instituted injection Streptopenicillin  5.0 g IM; injection Ceftriaxone and Tazobactam @ 5 mg/kg IM; injection  Meloxicam @ 0.2 mg/kg IM and antiseptic dressing of the prepuce was done with 5  % solution of Povidone iodine. All the bulls recovered uneventfully within a week  after treatment and were given sixty days of sexual rest after treatments to prevent  further injury and reoccurrence of the preputial prolapsed condition. The outcome  of present study suggests that the acute cases of 2nd degree preputial prolapse may  recover with medical management and do not need surgical intervention.
Keywords: Bull; Gir; Preputial prolapse; Fibrinous reaction; Therapeutic management